CIRI-CIRI KEPENGARANGAN DAN PENGGUNAAN LITERATUR DALAM MAJALAH INDONESIA BIDANG ILMU-ILMU SOSIAL - Sri Purnomowati (BACA: Jurnal Dokumentasi dan Informasi, 2025)
The pwpose of this study is to find out the authorship and the use of literature characteristics in social sciences. The result for the study of Masyarakat Indonesia (JSSN 0125-9989) consists a number of 12 publications with 67 articles showing that the authors were dominated by males. The most popular subjects written are social groups by age and ethnic, and labor economics. The average number of authorship per article is 1,09 and articles with multi authorship reaching 8,96% and author productivity being 9,23%. The average number of pages per article is 19,60 pages and each article containing 24,91 references. Books are the most used document for references, and median of all citation age is 11 years, while citation age in politics and economics are relatively current documents. Prisma is the most cited journal, while the most cited of Indonesian authors is Koentjaraningrat.